Apolipoprotein C-III: From Pathophysiology to Pharmacology. (October 2015) - Norata, Giuseppe Danilo; Tsimikas, Sotirios; Pirillo, Angela; Catapano, Alberico L.
<x xml:space="preserve">Abstract</x> Apolipoprotein C-III (apoC-III) has a critical role in the metabolism of triglyceride (TG)-rich lipoproteins (TRLs). Animal models lacking the APOC3 gene exhibit reduced plasma TG levels, whereas the overexpression of APOC3 leads to increased TG levels. In humans, loss-of-function mutations in APOC3 are associated with reduced plasma TG levels and reduced risk for ischemic vascular disease and coronary heart disease. Several hypolipidemic agents have been shown to reduce apoC-III, including fibrates and statins, and antisense technology aimed at inhibiting APOC3 mRNA to decrease the production of apoC-III is currently in Phase III of clinical development. Here, we review the pathophysiological role of apoC-III in TG metabolism and the evidence supporting this apolipoprotein as an emerging target for hypertriglyceridemia (HTG) and associated cardiovascular disorders.